«Полное собрание законов Российской империи» (зібрання третє) як джерело дослідження історії міста Глухова 1881–1913 рр. - Єсюнін, С.М. (Сіверщина в історії України, 2021)
Проаналізовано інформаційний потенціал законодавчих актів третього зібрання «Полного собрания законов Российской империи» для дослідження історії міста Глухова 1881–1913 рр. Зроблена систематизація виявлених матеріалів у таблицю. The article analyzes the information potential of the legislative acts of the third volume of the «Complete Collection of Laws of the Russian Empire» for 1881– 1913. The third collection consists of 33 volumes, totaling 29980 legislative acts during the reign of the emperors of the Russian Empire Alexander IІI and Nicholas IІ. Documents from the history of the city of Hlukhiv are revealed. The systematization of the detected materials in the table is made. A total of 24 documents were found in the second collection, covering various moments of the history of the city of Hlukhiv and Hlukhiv district. Among in this documents: the stay in city of Hlukhiv military units (1881, 1884); about military training of conscripts from the reserve (1887, 1888); the establishment of the police in Shostka of Hlukhiv district (1887); on the provision of a plot of land and a mill for a powder factory in Shostka of Hlukhiv district (1898); on elections to zemstvo assemblies and the State Duma (1890, 1907); on the introduction of martial law and mobilization during the Russo-Japanese War (1904, 1905). There are documents on the financing of the Hlukhiv men’s gymnasium (1909), оn the opening of the Hlukhiv district Guardianship of Orphanages of the Department of Institutions of the Empress Maria (1903), about the foundation and activity of the Tereshchenko city school (1892). Legislative acts of the second collection «Complete collection of Laws of Russian Empire», are important sources for studying the history of the city of Hlukhiv in the nineteenth century.